Results of the Global Youth Tobacco Survey and implementation of the WHO Framework Convention on Tobacco Control in the WHO Eastern Mediterranean Region (EMR) countries - Gulnoza Usmanova; Ali H. Mokdad (Springer, 2019)
We used Global Youth Tobacco Survey (GYTS) data collected over time to monitor articles of the World Health Organization Framework Convention on Tobacco Control (WHO FCTC) in WHO Eastern Mediterranean Region (EMR). Methods: The GYTS is a school-based survey, conducted in 23 countries in WHO EMR countries from 1999-2008. Results: The prevalence of current smokeless tobacco use was high compared to cigarette use in all countries. In general, the following changes were observed between baseline and repeated surveys: in five countries fewer youth supported a ban on smoking in public places. In four countries more youth saw actors smoking on TV and were exposed to second-hand smoke (SHS) outside of home. Fewer youth were offered free cigarettes in ten countries; in eight countries youth saw less advertisement on TV; in seven countries youth had fewer items with a tobacco logo, discussed more reasons for smoking and dangers of smoking, and were less exposed to SHS at home; in six countries youth saw less advertisement at sports events. Conclusion: The GYTS data can be used for monitoring, evaluation of national tobacco control plans and defining future directions for tobacco control.